Interferon Tau Affects Mouse Intestinal Microbiota and Expression of IL-17 - Wenkai Ren; Shuai Chen; Liwen Zhang; Gang Liu; Tarique Hussain; Xiao Hao; Jie Yin; Jielin Duan; Bie Tan; Guoyao Wu; Fuller W. Bazer; Yulong Yin (Mediators of Inflammation)
This study was conducted to explore the effects of interferon tau (IFNT) on the intestinal microbiota and expression of interleukin 17 (IL-17) in the intestine of mice. IFNT supplementation increased microbial diversity in the jejunum and ileum but decreased microbial diversity in the feces. IFNT supplementation influenced the composition of the intestinal microbiota as follows: (1) decreasing the percentage of Firmicutes and increasing Bacteroidetes in the jejunum and ileum; (2) enhancing the percentage of Firmicutes but decreasing Bacteroidetes in the colon and feces; (3) decreasing Lactobacillus in the jejunum and ileum; (4) increasing the percentage of Blautia, Bacteroides, Alloprevotella, and Lactobacillus in the colon; and (5) increasing the percentage of Lactobacillus, Bacteroides, and Allobaculum, while decreasing Blautia in the feces. Also, IFNT supplementation decreased the expression of IL-17 in the intestines of normal mice and of an intestinal pathogen infected mice. In conclusion, IFNT supplementation modulates the intestinal microbiota and intestinal IL-17 expression, indicating the applicability of IFNT to treat the intestinal diseases involving IL-17 expression and microbiota.